P.009 Improving Detection of Creutzfeldt-Jakob Disease Mimics in Clinical Practice. (November 2021) - Lazar, ES; Porter, AL; Prusinski, CC; Dunham, S; Lopez-Chiriboga, A; Hammami, M; Dubey, D; Day, GS
Abstract : Background: Assays capable of detecting prions in CSF (e.g., RT-QuIC) have greatly improved the antemortem diagnosis of Creutzfeldt-Jakob disease (CJD) yet take time to conduct and are not widely accessible. There is a need to identify clinical features and common tests that identify mimics at presentation. Methods: Mimics were identified within longitudinal studies of rapidly progressive dementia at study sites. Mimics met clinical criteria for probable CJD but did not have CJD. Clinical features were compared between mimics and patients with CJD assessed at Mayo Clinic Enterprise (n=79) and Washington University in St. Louis (n=10; Jan-2014 to Oct-2020). Results: Mimics (10/155; 6.5%) were diagnosed with autoimmune encephalitis (n=7), neurosarcoidosis, frontotemporal lobar degeneration with motor neuron disease, and unknown dementia. Age-at-symptom onset, gender, presenting symptoms, and EEG and MRI findings were similar between mimics and CJD patients. Focal motor abnormalities (49/93, 10/10), elevations in CSF leukocytosis (4/92, 5/10) and protein (39/92, 9/10) were more common in mimics (p<0.01). Neural-specific autoantibodies associated with autoimmune encephalitis were detected within the serum (4/9) and CSF (5/10) of mimics, but not CJD cases. Conclusions: Autoimmune encephalitis, neurosarcoidosis and neurodegenerative diseases may mimic CJD at presentation and should be considered in patients with early motor dysfunction and abnormal CSF studies.